Multi-cloud strategy for cloud architects : learn how to adopt and manage public clouds by leveraging baseops, finops, and devsecops /: learn how to adopt and manage public clouds by leveraging baseops, finops, and devsecops. (2023) - Mulder, Jeroen
No abstract available